A Critical Analysis of Maulana Shibli Nomani’s Educational Thoughts - Razia Sultana (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
Maulana Shibli Nomani (1857–1914) was a distinguished Islamic scholar, historian, philosopher and reformer in British India. A key figure in the Aligarh and Nadwa movements, he played a pivotal role in advancing Muslim education and intellectual renewal. Shibli emphasized blending traditional Islamic learning with modern education, advocating for the study of modern sciences, humanities, and the English language. Shibli aimed to bridge the gap between traditional scholars and modern thinkers within Muslim society. At Nadwat al-Ulama, he reformed the curriculum to include English, Hindi, and Sanskrit alongside Islamic studies, fostering a holistic approach to learning. He also established the Dar al-Musannefin in Azamgarh to promote Urdu scholarship and make classical texts accessible to wider audiences.Although he faced criticism from both conservative and liberal groups, Shibli's writings, such as Maqalat-e-Shibli, celebrated the intellectual achievements of early Muslim scholars and highlighted the need for a balanced education. He supported female education, though his views were tempered by the social norms of his time. Shibli's legacy lies in his vision for gradual yet transformative educational reform. His efforts continue to inspire intellectual growth and social cohesion among Indian Muslims during a period of profound change.